Book Review - Brigitte Le Normand, Citizens Without Borders: Yugoslavia and Its Migrant Workers in Western Europe Toronto: Toronto University Press, 2021, 286 pp. - Miha Zobec (Dve Domovini, 2023)
In analyzing states’ responses to human mobilities, migration studies have long focused on the role played by the states that received migrants. However, scholarship examining governments’ outreach toward emigrants has been expanding, and Brigitte Le Normand’s book Citizens Without Borders falls precisely into this emerging field. Le Normand, a historian of Southeast Europe and a migration scholar at Maastricht University (who previously held a position at the University of British Columbia, Canada), employs new trends in migration research to shed light on how socialist Yugoslavia monitored its emigrant workers, i.e., migrants who, in the official discourse, were referred to as “workers temporarily working abroad.”